The Birth of modern theatre Chekhov's Uncle Vanya in perspective - Mantell, Harold; Olivier, Laurence (History of drama / produced by Harold Mantele., 1975)
Analyzes Chekhov's dramatic techniques as developed in Uncle Vanya. Includes a performance of the third act of the English translation by Constance Garnett.